Numerical investigation of heat transfer and friction factor characteristics of circular tube fitted with an array of semi-elliptical vortex generator inserts. Issue 1 (1st January 2021) - M.S, Manjunath; Fernandes, Dolfred Vijay
Abstract: This article presents the heat transfer and friction factor characteristics of circular tube fitted with an array of novel semi-elliptical vortex generator inserts using air as working fluid. The study makes use of computational fluid dynamics methodology and the influence of varying aspect ratio (AR = 1, 2, 4 and 6), flow attack angle (45°, 60°, 75° and 90°) and longitudinal pitch (P = 30 mm, 60 mm and 90 mm) of vortex generator is investigated for the turbulent flow Reynolds number regime of 8000–26000. The numerical results reveal that the presence of semi-elliptical vortex generator has significant influence on both Nusselt number and friction factor characteristics of circular tube. The vortex generators produce strong longitudinal vortices which intensifies fluid mixing near the tube wall region thereby augmenting the heat transfer to the flowing air stream. In addition, the presence of flow impingement effect on the upstream side and flow reattachment zones on the downstream side of vortex generator is found to contribute to enhanced heat transfer. The influence of aspect ratio on heat transfer is found to be more significant than that of flow attack angle. However, both parameters affect the friction factor significantly. On the other hand, the pitch distance of insert significantly affects both heat transfer and friction factor. The maximum rise in Nusselt number and friction factor is about 2.1 times and 6.34 times higher than plain tube, respectively, for P = 30 mm. The thermal enhancement factor (TEF) is found to decrease with increasing flow attack angle and aspect ratio for all flow rates considered in the study. However, the TEF increases with decreasing pitch distance of inserts and the overall TEF is found to be in the range of 0.86–1.19.